SP1‐mediated upregulation of LINGO‐1 promotes degeneration of retinal ganglion cells in optic nerve injury. (19th June 2020) - Wu, Yali; Zhan, Zongyi; Quan, Yadan; Yang, Yangfan; Chen, Xiaotao; Liu, Liling; Wu, Kaili; Yu, Minbin
Abstract: Backgrounds: Insults to the axons in the optic nerve head are the primary cause of loss of retinal ganglion cells (RGCs) in traumatic, ischemic nerve injury or degenerative ocular diseases. The central nervous system–specific leucine‐rich repeat protein, LINGO‐1, negatively regulates axon regeneration and neuronal survival after injury. However, the upstream molecular mechanisms that regulate LINGO‐1 signaling and contribute to LINGO‐1–mediated death of RGCs are unclear. Methods: The expression of SP1 was profiled in optic nerve crush (ONC)–injured RGCs. LINGO‐1 level was examined after SP1 overexpression by qRT‐PCR. Luciferase assay was used to examine the binding of SP1 to the promoter regions of LINGO‐1. Primary RGCs from rat retina were isolated by immunopanning and RGCs apoptosis were determined by Tunnel. SP1 and LINGO‐1 expression was investigated using immunohistochemistry and Western bolting. Neuroprotection was assessed by RGC counts, RNFL thickness, and VEP tests after inhibition of SP1 shRNA. Results: We demonstrate that SP1 was upregulated in ONC‐injured RGCs. SP1 was bound to the LINGO‐1 promoter, which led to increased expression of LINGO‐1. Treatment with recombinant Nogo‐66 or LINGO‐1 promoted apoptosis of RGCs cultured under serum‐deprivation conditions, while silencing of SP1 promoted the survival of RGCs. SP1 and LINGO‐1 colocalized and were upregulated in ONC‐injured retinas. Silencing of SP1 in vivo reduced LINGO‐1 expression and protected the structure of RGCs from ONC‐induced injury, but there was no sign of recovery in VEP. Conclusions: Our findings imply that SP1 regulates LINGO‐1 expression in RGCs in the injured retina and provide insight into mechanisms underlying LINGO‐1–mediated RGC death in optic nerve injury.